Manajemen Keuangan dalam Pemenuhan Fasilitas Pendidikan Kampus Berbasis Pesantren - Siti Nur Azizah; Siti Aimah; M. Imam Khaudli; Abdulloh Hamid; Nur Hidayatulloh (Instructional Development Journal, 2024)
This research aims to analyze and understand financial management in fulfilling Islamic boarding school-based campus education facilities at KH University. Mukhtar Syafaat Blokagung Banyuwangi. This research uses a qualitative case study type approach. The data collection technique uses in-depth interviews, participant observation and corroborating documents. The data validation uses triangulation and data analysis uses Miles and Huberman's three interactive models, namely data reduction, data display and conclusion drawing. The research results show that financial management innovation at KH University. Mukhtar Syafaat consists of; 1) Integrated Syahriyah 2) SIS as a payment information application. 3) Payments using financial digitalization, namely BRI virtual account (BRIVA). 4) Cashless as a non-cash transaction tool. Payment transparency at KH University. Mukhtar Syafaat can be tracked and accessed. Budget transformation at KH University. Mukhtar Intercession; 1) Budget evaluation every 2 years. 2) Increase the budget according to needs. Strategy for fulfilling educational facilities at KH University. Mukhtar Syafaat gradually progresses to fulfilling priority facilities and then supporting facilities. As for the evaluation of educational facilities at KH University. Mukhtar Syafaat consists of; 1) procurement of educational facilities. 2) Maintenance of educational facilities. 3) elimination of educational facilities